2017
DOI: 10.7189/jogh.07.020414
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge about mother–to–child transmission of HIV, its prevention and associated factors among Ethiopian women

Abstract: BackgroundPoor awareness and knowledge of mother–to–child transmission (MTCT),that accounts for over 90% of new HIV infections among children, might contribute to the HIV epidemics. In Ethiopia, 898 400 children are orphaned due to HIV and AIDS and 200 300 were living with HIV in 2013. The main objective of this study was to examine the knowledge of MTCT of HIV, its prevention (PMTCT) and associated factors among Ethiopian women.MethodsWe conducted a cross–sectional analysis among 16 515 women from the Ethiopi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

35
42
8
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(86 citation statements)
references
References 14 publications
(13 reference statements)
35
42
8
1
Order By: Relevance
“…Luba and others also found out that the women from emerging regions being less likely to have sufficient knowledge on MTCT of HIV compared to those reside in city administration and Harari region [28], which is in agreement with this study. This could be due to the long distance of the emerging region from the central government.…”
Section: Distribution Of Socio-demographic Characteristics Among Womesupporting
confidence: 91%
See 3 more Smart Citations
“…Luba and others also found out that the women from emerging regions being less likely to have sufficient knowledge on MTCT of HIV compared to those reside in city administration and Harari region [28], which is in agreement with this study. This could be due to the long distance of the emerging region from the central government.…”
Section: Distribution Of Socio-demographic Characteristics Among Womesupporting
confidence: 91%
“…This could be because the low level of knowledge on MTCT among the poor women might be due to financial problems and so less access to health services and health information related to MTCT of HIV. This is in line with the study from 2011 Ethiopian DHS data that women from the richest household were 1.85 times more likely to have sufficient knowledge towards MTCT compared to the poorest women [28].…”
Section: Distribution Of Socio-demographic Characteristics Among Womesupporting
confidence: 91%
See 2 more Smart Citations
“…Published studies have shown the importance of correct comprehensive maternal knowledge of MTCT and PMTCT in the fight against new pediatric HIV infections [7][8][9]. Correct comprehensive maternal knowledge and knowing places offering HIV testing correlates positively with maternal HIV testing [7]; it also increases access to HIV tests and maternal understanding of the risks of HIV infections [10].…”
Section: Introductionmentioning
confidence: 99%